DESCRIPTION OF PLANKTON OF SHALLOW PART OF NORTH CASPIAN SEA - R. I. Umerbayeva; N. V. Popova; N. A. Sargsyan (Юг России: экология, развитие)
Data for the five years on a plankton in shallow water of Northern Caspian sea is cited in work, the problem of quantity indicators of development of a plankton, long-term dynamics is discussed.